2018
DOI: 10.3389/fmars.2018.00484
|View full text |Cite
|
Sign up to set email alerts
|

Remobilization of Heavy Metals by Mangrove Leaves

Abstract: Several studies have been carried out on heavy metal pollution in mangrove ecosystems. However, the role of mangroves in heavy metal remobilization is still relatively unknown. On one side, mangrove woody organs and soils sequester heavy metals for long time periods, but on the other hand, senescence of mangrove leaves may return these metals collected by roots to the upper layers of the soil. Here, we analyzed the concentration of chemical elements (Al, As, Cd, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Sr, V, and Zn) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…However, sediments were extremely enriched with Sr (Abrahim and Parker, 2008). Similar concentrations of heavy metals to the concentrations in this present study except V were also reported from other locations in central Red Sea and northern and southern parts of the Red Sea (Hanna, 1992;Fowler et al, 1993;Badr et al, 2009;Soliman et al, 2015;Abu-Zied and Hariri, 2016;Youssef and El-Sorogy, 2016;Ruiz-Compean et al, 2017;Almahasheer et al, 2018). This suggests that the six mangrove ecosystems investigated in this study might not be under severe heavy metal pollution despite the different anthropogenic activities going on in these ecosystems and their catchment.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, sediments were extremely enriched with Sr (Abrahim and Parker, 2008). Similar concentrations of heavy metals to the concentrations in this present study except V were also reported from other locations in central Red Sea and northern and southern parts of the Red Sea (Hanna, 1992;Fowler et al, 1993;Badr et al, 2009;Soliman et al, 2015;Abu-Zied and Hariri, 2016;Youssef and El-Sorogy, 2016;Ruiz-Compean et al, 2017;Almahasheer et al, 2018). This suggests that the six mangrove ecosystems investigated in this study might not be under severe heavy metal pollution despite the different anthropogenic activities going on in these ecosystems and their catchment.…”
Section: Discussionsupporting
confidence: 89%
“…The plant-sediment interaction based on metal accumulation is better estimated using the BCF. However, the BCFs for all the 13 metals were <1, suggesting an effective mechanism of detoxification or exclusion by A. marina (Almahasheer et al, 2018;Aljahdali and Alhassan, 2020a). In addition, it should be noted that some heavy metals determined in this study such as Fe, Cu, Mn, and Mo are essential for plant growth, if not in excess or above a limit where they become toxic (Appenroth, 2010).…”
Section: Metals In Mangrove a Marina And Bcfmentioning
confidence: 61%
See 1 more Smart Citation
“…As mangroves naturally accumulate compounds from their environments, many pollutants are incorporated into the plant’s tissues 46 . These then have the potential to be subsequently remobilized when those tissues degrade, with greater bioavailability than those held in sediments 47 . The presence of pollutants will also alter the microbial community associated with the water column, sediment, and plant material 44 , 48 , which could further impact litter decomposition and associated chemical cues.…”
Section: Introductionmentioning
confidence: 99%
“…The BCF of Cu in Pluchea indica was > 1 (Soraya et al 2019). Despite considered as heavy metal, Zn is one of the essential micronutrients for plant growth and nontoxic (Appenroth 2010;Almahasheer et al 2018). However, the Zn can be toxic for plant if the Zn exceeds the plant toxicity threshold which is 300-600 mg/kg (Long et al 2003).…”
Section: Introductionmentioning
confidence: 99%